Microwave-assisted Cu(I)-catalyzed, three-component synthesis of 2-(4-((1-phenyl-1H-1,2,3-triazol-4-yl)methoxy)phenyl)-1H-benzo[d]imidazoles - Kumar, Yogesh; Bahadur, Vijay; Singh, Anil Kumar; Parmar, Virinder Singh; Van der Eycken, Erik V.; Singh, Brajendra Kumar (Beilstein Journal of Organic Chemistry, 2014)
A microwave-assisted synthesis of 2-(4-((1-phenyl-1H-1,2,3-triazol-4-yl)methoxy)phenyl)-1H-benzo[d]imidazoles from a phenylazide, propargyloxybenzaldehyde and a 1,2-diaminobenzene is proposed.
Keywords: benzimidazole; Cu(I) catalysis; microwave-assisted synthesis; multicomponent; three component synthesis